TRANSPARENT AND ACCOUNTABLE SCHOOL FINANCIAL MANAGEMENT: CHALLENGES AND PROCESSES - Dwi Koerniawati; Al-Amin (Adisam Publisher, 2026)
Transparent and accountable school financial management is an important aspect in ensuring the sustainability and credibility of educational institutions. Transparency enables effective oversight and reduces the risk of misappropriation of funds, while accountability ensures that any funds utilised can be accounted for to all stakeholders. However, significant challenges are often faced, including limited skilled human resources, differences in standards and regulations between different levels of government, and limitations in technology and infrastructure. Overcoming these challenges requires improving the capacity of human resources through regular training and appropriate application of information technology, as well as strong collaboration between schools, government and communities. Thus, more open and accountable financial management can be achieved, supporting sustainable educational progress.